Basic researchIn vitro neural/glial differentiation potential of periodontal ligament stem cells - Li, Xiaojie; Gong, Ping; Liao, Dapeng (Archives of Medical Science, 2010)
Introduction : It is known that periodontal ligament stem cells (PDLSCs) can differentiate into cementoblast-like cells, adipocytes and collagen-forming cells. However, whether PDLSCs are able to differentiate into Schwann cells and which method is best for their neural induction remain unknown. We attempted to determine whether PDLSCs possessed the potential for neural differentiation in vitro . Materials and methods : We isolated and multiplied PDLSCs from periodontal ligaments obtained from the teeth (n = 24) of 8-month-old beagle dogs. Four protocols with different chemicals and growth factors were adopted to induce the PDLSCs to differentiate into Schwann cells. Immunochemistry, RT-PCR and qRT-PCR were performed to investigate the in vitro neural differentiation potential of PDLSCs. Results : We compared the 4 different protocols and showed that all 4 protocols could successfully induce PDLSCs to express nestin, GFAP and S100, markers for Schwann cells. Further, qRT-PCR revealed relative differences in the expression levels of these 3 genes in differentiated PDLSCs obtained by different protocols. Conclusions : We conclude that PDLSCs have neural/glial differentiation potential in vitro and that neural/glial differentiation can be induced in PDLSCs if suitable protocols are followed. We also found that supplementing the growth medium with suitable growth factors is more effective than applying chemicals alone. While nerve growth factor is more effective than platelet-derived growth factor for inducing neural/glial differentiation in PDLSCs, pre-induction of PDLSCs with dimethyl sulphoxide yields better results than those obtained with all-trans-retinoic acid.